ANALISIS KELAYAKAN USAHA BUDIDAYA GAHARU, STUDI KASUS DI KABUPATEN PULANG PISAU PROVINSI KALIMANTAN TENGAH (Feasibility Analysis of Gaharu. Case Study at Pulang Pisau District, Central Kalimantan Province): Herna Widyarini1), Wahyudi2), Renhart Jemi2 - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTGaharu is non timber forest product in the form of the rotted xylem of which yields fragrant resinous material that produced from gaharu trees or tree eaglewood as Aquilaria spp. Gaharu trees are suitable planted at the degraded peat-swamp forest that widely contained at the Central Kalimantan Province. This research was aimed to analyze the feasibility of gaharu planted at the peat-swamp forest in Jabiren Raya sub District, Pulang Pisau District, Central Kalimantan Province. The research was conducted at the gaharu (Aquilaria malaccensis) plantation aged 1 to 6 years old. Inoculation of stems and harvesting were done at the moment aged 5 and 6 years old respectively. Data analysis using NPV, BCR, and IRR with the assumption using internl and external fund at the 7.5%, 7.75%, and 12% of rate. Research result showed that gaharu cultivation is feasible with NPV, BCR, and IRR namely IDR 92.51 mill, 1.34, and 0.1686 respectively at the 7.5% of rate. At the rate of 7.75%, NPV, BCR, and IRR namely IDR 89.07 mill, 1.33, and 0.1686 respectively, and at the rate of 12%, NPV, BCR, and IRR namely IDR 40.46 mill, 1.17, and 0.1686 respectively. The value of IRR showed that gaharu cultivation is feasible conducted at the rate under 16.86%.Keywords: external and internal fund, feasibility,gaharu